Phenolic and bisamide derivatives from Aglaia odorata and their biological activities - Xiaomeng Yang; Yan Yu; Panfeng Wu; Juan Liu; Yanan Li; Linlan Tao; Rong Tan; Xiaojiang Hao; Chunmao Yuan; Ping Yi (Natural Product Research, 2023)

Long-term crowding stress induces chronic inflammatory response and declines the immunity of grass carp (Ctenopharyngodon idella) - Wenhan Li; Dapeng Li; Qiushi Yang; Lu Liu; Jieya Liu; Jiamin Lu; Yin Wang; Rong Tang; Li Li; Xi Zhang (Aquaculture, 2023)

Relative contribution of roots and symbiotic fungi to wheat nitrogen uptake and N2O emissions under straw burial - Zheng-Rong Kan; Yanling Li; Ruoyan Yang; Xinyu Yang; Qihang Wei; Ahmad Latif Virk; Jianying Qi; Feng-Min Li; Zichang Zhang; Haishui Yang (Rhizosphere, 2023)

Comparative study on characteristics of typhoon gusts in the coastal and offshore areas of the South China Sea - Qian-Jin Zhou; Lei Li; Shao-Jia Fan; Hong-Long Yang; Wei Sun; Hai-Rong Tang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Complete genome analysis of type strain of a novel bacterial family Temperatibacteraceae fam. nov., isolated from surface seawater - Jin-Cheng Rong; Lin-Lin Cui; Xiao-Chen Yang; Mao-Li Yi; Qi Zhao (Marine Genomics, 2023)

Carbon-neutral potential in treatment of N, N-dimethylformamide-containing industrial wastewater: Comparative investigation of energy conservation, carbon reduction and expenditure between UASB and Fenton process - Xinwei Tan; Yuqin Fan; Xinzheng Zhang; Tianwei Hao; Rong Chen; Tao Zhang; Rui Lu; Jianliang Sun; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2023)

Metabolic cross-feeding enhances branched-chain aldehydes production in a synthetic community of fermented sausages - Kaihao Liu; Peng Yang; Xudong Zhang; Di Zhang; Liu Wu; Lan Zhang; Huan Zhang; Guoliang Li; Ruren Li; Liangyan Rong (International Journal of Food Microbiology, 2023)

Fracture and porosity evolution of coal under uniaxial compression: An in-situ X-ray tomography study - Yanbin Yu; Zhaoxu Qiu; Weimin Cheng; Qi Yang; Wenting Cui; Kang Rong; Yunfei Li (Geomechanics for Energy and the Environment, 2023)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Analysis of mRNA and MicroRNA Expression Profiles of Nervous Tissues and Reproductive Tissues in Male Procambarus clarkii After Silencing IAG - Rong Sun; Shaokui Yi; Linlin Shi; Kianann Tan; Ruixue Shi; Siqi Yang; Yanhe Li (Marine Biotechnology, 2023)

Morphological and Pull-Out Mechanical Properties of Alfalfa Roots in the Seedling Stage - Chaobo Zhang; Rong Li; Jing Jiang; Qihong Yang (Journal of Soil Science and Plant Nutrition, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Endophytic Bacillus sp. R1 and Its Roles in Assisting Phytoremediation and Alleviating the Toxicity of Aluminum Combined Phenanthrene Contaminations in Brassica napus - Li-rong Fang; Xue-cheng Yang; Chun-ya Wu; Kai Sun; Mallavarapu Megharaj; Wei He (Current Microbiology, 2023)

Rhizosphere shapes the associations between protistan predators and bacteria within microbiomes through the deterministic selection on bacterial communities - Yang Yue; Chen Liu; Boting Xu; Yijin Wang; Qihui Lv; Zeyuan Zhou; Rong Li; George A. Kowalchuk; Alexandre Jousset; Qirong Shen; Wu Xiong (Environmental Microbiology, 2023)
The assembly of bacterial communities in the rhizosphere is well‐documented and plays a crucial role in supporting plant performance. However, we have limited knowledge of how plant rhizosphere determines the assembly of protistan predators and whether the potential associations between protistan predators and bacterial communities shift due to rhizosphere selection. To address this, we examined bacterial and protistan taxa from 443 agricultural soil samples including bulk and rhizosphere soils. Our results presented distinct patterns of bacteria and protistan predators in rhizosphere microbiome assembly. Community assembly of protistan predators was determined by a stochastic process in the rhizosphere and the diversity of protistan predators was reduced in the rhizosphere compared to bulk soils, these may be attributed to the indirect impacts from the altered bacterial communities that showed deterministic process assembly in the rhizosphere. Interestingly, we observed that the plant rhizosphere facilitates more close interrelationships between protistan predators and bacterial communities, which might promote a healthy rhizosphere microbial community for plant growth. Overall, our findings indicate that the potential predator–prey relationships within the microbiome, mediated by plant rhizosphere, might contribute to plant performance in agricultural ecosystems.

First principles insights into the interaction mechanism of iron doped thermally activated kaolinite with Cd and Pb pollutants in organic solid waste incineration flue gas - Yang-wen Wu; Rong Guo; Li-juan Sun; Xin-yue Zhou; Jia-le Zhou; Hai-yuan Zhao; Yi-fei Yu; Zhuang Hu; Bin Hu; Ji Liu; Bing Zhang; Li Zhao; et al. (Waste Management, 2023)

Experimental infection and co-infection with Chinese strains of Ehrlichia canis and Babesia vogeli in intact and splenectomized dogs: Insights on clinical, hematologic and treatment responses - Jilei Zhang; Jiawei Wang; Patrick John Kelly; Yuanyuan Zhang; Min Li; Jing Li; Rong Zhang; Yaoyao Wang; Ke Huang; Jinfeng You; Haixiang Qiu; Xiaofeng Zheng; et al. (Veterinary Parasitology, 2023)

Evolution of biogenic Fe-Mn binary oxide physicochemical properties during biofilter start-up for sustainable urban groundwater treatment - Haiyang Yang; Huarong Yu; Minhua Zeng; Heng Liang; Hongwei Rong; Guibai Li; Fangshu Qu (Sustainable Cities and Society, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Characteristics of landscape and erosion in the Eastern Pamir and their implications for regional fault connections - Yunpeng Wu; Rong Yang; Junqing He; Hanlin Chen; Xiubin Lin; Xuhua Shi; Kaixuan An; Chunyang Li; Shibao Gao; Yaguang Chen (Geomorphology, 2023)

Climatic aridification restrained late Cenozoic denudation of the Tian Shan in the inland of Asia - Yutong Jiang; Honghua Lu; Ruohong Jiao; Lichen Pang; Rong Yang; Menghan Wu; Xiangmin Zheng; Youli Li (Global and Planetary Change, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Fabrication of natural W1/O/W2 double emulsions stabilized with gliadin colloid particles and soybean lecithin - Xuan Zhang; Xing Rong; Duo Zhang; Yongkang Yang; Bin Li (Food Hydrocolloids, 2023)

Fabrication of depolymerized zein films via high-intensity ultrasound for ethylene adsorption packaging - Xin Fan; Ting Yang; Yuxin Li; Jinghua Zhao; Lingshuang Rong; Li Feng; Junrong Huang (Food Packaging and Shelf Life, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Quantum chemical calculation assisted efficient lithium extraction from unconventional oil and gas field brine by β-diketone synergic system - Yunze Zhao; Huifang Xing; Meng Rong; Zheng Li; Xuetuan Wei; Congmei Chen; Huizhou Liu; Liangrong Yang (Desalination, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Nanoparticle (NP)-mediated APOC1 silencing to inhibit MAPK/ERK and NF-κB pathway and suppress breast cancer growth and metastasis - Shaomin Liu; Fengqian Zhang; Yixia Liang; Guo Wu; Rong Liu; Xiuling Li; Phei Er Saw; Zhonghan Yang (Science China Life Sciences, 2023)

Blockade of the Dopamine D3 Receptor Attenuates Opioids-Induced Addictive Behaviours Associated with Inhibiting the Mesolimbic Dopamine System - Rong-Rong Hu; Meng-Die Yang; Xiao-Yan Ding; Ning Wu; Jin Li; Rui Song (Neuroscience Bulletin, 2023)

Quantification of multiple environmental controls on lipid biomarkers in common marine diatoms and dinoflagellates - Zhong Cao; Rong Bi; Chuanli Zhang; Jiaxuan Cui; Li Li; Yang Ding; Meixun Zhao (Marine Biology, 2023)

Feeding-induced plant metabolite responses to a phoretic gall mite, its carrier psyllid and both, after detachment - Mengke Yang; Jianling Li; Haili Qiao; Kun Guo; Rong Xu; Hongshuang Wei; Jianhe Wei; Sai Liu; Changqing Xu (Experimental and Applied Acarology, 2023)

High phytoplankton diversity in eutrophic states impedes lake recovery - Rong Wang; C. Patrick Doncaster; Wenxiu Zheng; Min Xu; Hui Yang; Yun Li; Yongjiu Cai; Yanjie Zhao; Enlou Zhang; Xiangdong Yang; Boqiang Qin (Journal of Biogeography, 2023)
Aim The widely observed positive response of productivity to biodiversity, known as the biodiversity‐productivity relationship (BPR), underpins nature‐based solutions for mitigating and adapting to global changes. Little is known of the role of such emergent processes in the restoration of damaged ecosystems. Here, we test for evidence of a BPR in degraded freshwater lakes, and its role in underpinning or undermining lake recovery from eutrophic states. Location Lower Yangtze and Huaihe river basins, China, East Asia. Taxa Freshwater phytoplankton; also macrophytes, fish, zooplankton and zoobenthos. Methods A systematic review of biodiversity studies was conducted to enumerate freshwater biodiversity change during eutrophication, encompassing 572 samples from 155 lakes in East China. Empirical samples were then taken of 93 phytoplankton communities from 38 lakes in ecologically degraded states of eutrophication. Samples were analysed for niche overlap in relation to biodiversity and productivity, and metrics of network structure indicative of community stability. Results Reviewed publications on eutrophication in East China lakes revealed losses in biodiversity of macrophytes, fishes, zooplankton and zoobenthos but not phytoplankton. Empirically sampled eutrophic lakes maintained high phytoplankton biodiversity through niche differentiation, and phytoplankton biodiversity correlated positively with biomass, in line with the expectations of BPR. Conclusions The positive effect of biodiversity on phytoplankton productivity in eutrophic lakes acts in opposition to the negative impacts on productivity induced by eutrophication‐management strategies of nutrient suppression. In degraded systems, the BPR contributes to sustaining productivity of lake phytoplankton communities, impeding recovery from a eutrophic state. This is a case of the BPR playing an undesirable role at the ecosystem level. Lake recovery programmes need to anticipate that the control of phytoplankton biomass will depend on reducing nutrients to a level sufficient to degrade the internal structure of the phytoplankton community.

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

N, N-bis (2-hydroxyethyl) malonamide based amidoxime functionalized polymer immobilized in biomembranes for highly selective adsorption of uranium(VI) - Yang Li; Ze-Yang Wang; Qi Ren; Feng Zhang; Xu-Xin Li; Qiang Wu; Rong Hua; Ze-Yi Yan; Yun Wang (Chemosphere, 2023)

Effect of iron-loaded sludge biochar amendments on phytoremediation potential of Cr-contaminated soils by Leersia hexandra swartz - Jin-Chao Wang; Ji-Rong Zhao; Qing-Xia Huang; Li-Jiao Yang; Guo Yu; Yu-Feng Xu; Li-Heng Liu (Chemosphere, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Ferrous ion enhanced Fenton-like degradation of emerging contaminants by sulfidated nanosized zero-valent iron with pH insensitivity - Jia-Qi Chen; Guan-Nan Zhou; Rong-Rong Ding; Qi Li; Han-Qing Zhao; Yang Mu (Journal of Hazardous Materials, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

Effect of peach trichome removal on post-harvest brown rot and on the fruit surface microbiome - Youming Shen; Xinna Li; Rong Xiong; Yang Ni; Shiping Tian; Boqiang Li (International Journal of Food Microbiology, 2023)

The role of total antioxidant capacity and malondialdehyde of seminal plasma in the association between air pollution and sperm quality - Lipeng Li; Tengfei Feng; Ruiting Wu; Yaling Zhang; Ning Wang; Mengqi Wu; Yaxian Pang; Sujuan Yang; Aimin Yang; Dengsuo Zhang; Guimin Hao; Rong Zhang (Environmental Pollution, 2023)

Regulating dynamic equilibrium of active hydrogen for super-efficient nitrate electroreduction to ammonia - Yang Gao; Rong Wang; Yudong Li; Enshan Han; Maosen Song; Ziyi Yang; Feng Guo; Yanzhen He; Xiaohui Yang (Chemical Engineering Journal, 2023)

Forest degradation caused by dwarf bamboo overabundance reduces soil C, N and P stocks in giant panda habitat - Li Mo; Hao Yang; Rong Hou; Wei Wu; Xinqiang Song; Hong Yang; Zhisong Yang; Weichao Zheng; Dunwu Qi (CATENA, 2023)

Insights into roles of triclosan in microalgal–bacterial symbiosis system treating wastewater - Cong-Cong Tang; Tian-Yang Wang; Rong Wang; Cristiano Varrone; Zixuan Gan; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Bioresource Technology, 2023)

Neuroglobin Facilitates Neuronal Oxygenation through Tropic Migration under Hypoxia or Anemia in Rat: How Does the Brain Breathe? - Chun-Yang Li; Hai-Feng Jiang; Li Li; Xiao-Jing Lai; Qian-Rong Liu; Shang-Bin Yu; Cheng-La Yi; Xiao-Qian Chen (Neuroscience Bulletin, 2023)

Balanced phosphorus fertilization enhances soil bacterial network complexity to maintain multifunctionality and plant production in dryland agricultural systems - Lei Liu; Rong Yan; Li Zhu; Yu Yang; Zhiyuan Gao; Wenjie Yang; Jinshan Liu (Agriculture, Ecosystems & Environment, 2023)

Short-term feeding of dietary florfenicol influences gut microbiome and growth performance of fast-growing Silurus meridionalis - Zhimin Zhang; Qiushi Yang; Weitong Xu; Rong Tang; Li Li; Dapeng Li (Aquaculture, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Multiscale CFD modelling for conformal atomic layer deposition in high aspect ratio nanostructures - Yuanxiao Chen; Zoushuang Li; Ziao Dai; Fan Yang; Yanwei Wen; Bin Shan; Rong Chen (Chemical Engineering Journal, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Arbuscular mycorrhizal fungi mitigate earthworm-induced N2O emissions from upland soil in a rice-rotated wheat farming system - Zheng-Rong Kan; Qihang Wei; Ruoyan Yang; Yanling Li; Jiajia Zhou; Jianying Qi; Feng-Min Li; Haishui Yang (Applied Soil Ecology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Method for quantitative extraction of copper hydroxide nanoparticles from farmland soil - Xin-Yuan Li; Yuan Yang; Peng Huang; Ying-Rong Wang; Yu-Lin Nie; Li Zhang; Qiang Wang (Science of The Total Environment, 2023)

Detection of spatiotemporal changes in ecological quality in the Chinese mainland: Trends and attributes - Yang Li; Haifeng Tian; Jingfei Zhang; Siqi Lu; Zhixiang Xie; Wei Shen; Zhicheng Zheng; Mengdi Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Effects of dietary supplementation of Anabaena sp. PCC7120 expressing VP28 protein on survival and histopathology after WSSV infection in Macrobrachium nipponense - Yupei Tong; Jia Yang; Li Wang; Xiaoping Chi; Chan Zhu; Rong Yin; Le Zhang; Yaru Li; Chunyan Zhao; Rui Jia (Fish & Shellfish Immunology, 2023)

Shape Classification of Cloud Particles Recorded by the 2D-S Imaging Probe Using a Convolutional Neural Network - Rong Zhang; Haixia Xiao; Yang Gao; Haizhou Su; Dongnan Li; Lei Wei; Junxia Li; Hongyu Li (Journal of Meteorological Research, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

Effects of discharge angle of jet from a slot orifice on cooling performance for a perforated air ducting system in dairy cattle barn - Mengbing Cao; Ruimin Yang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Kaiying Wang; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Hydroclimate changes since the last glacial maximum from sedimentary biomarkers in a crater lake in the Great Khingan Mountains, Northeast China - Weiwei Sun; Enlou Zhang; Enfeng Liu; Yang You; Jingjing Li; Zhenyu Ni; Xianqiang Meng; Wenfang Zhang; Rong Chen (Quaternary Science Reviews, 2023)

Effect of flue gas components on the removal of cadmium pollutants by transition metal-modified activated carbon: Density functional theory and thermodynamic study - Xin-Yue Zhou; Jia-Le Zhou; Rong Guo; Yin-jie Liu; Yi-fei Yu; Bing Zhang; Yang-Wen Wu; Li Zhao; Qiang Lu (Fuel, 2023)

Corrigendum to “Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels” [Food Hydrocolloids 139 (2023) 108527] - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Amorphous biomineral-reinforced hydrogels with dramatically enhanced toughness for strain sensing - Jia-hua Liu; Zhengyi Mao; Yuhan Chen; Yunchen Long; Haikun Wu; Junda Shen; Rong Zhang; Oscar W.H. Yeung; Binbin Zhou; Chunyi Zhi; Jian Lu; Yang Yang Li (Chemical Engineering Journal, 2023)

Investigating the thermal conductivity and flame-retardant properties of BN/MoS2/PCNF composite film containing low BN and MoS2 nanosheets loading - Lei Yang; Wei Xu; Xiaolong Shi; Menglin Wu; Ziyi Yan; Qing Zheng; Gongneng Feng; Li Zhang; Rong Shao (Carbohydrate Polymers, 2023)

Spatiotemporal characteristics of extreme hydrometeorological events and its potential influencing factors in the Huaihe River Basin, China - Rong Gan; Dandan Li; Changzheng Chen; Feng Yang; Xinyu Zhang; Xiaomin Guo (Stochastic Environmental Research and Risk Assessment, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Synergistic effect of elevated glucose levels with SARS-CoV-2 spike protein induced NOX-dependent ROS production in endothelial cells - Jiahao Zhang; Li He; Rong Huang; Juan Felipe Alvarez; David H. Yang; Qihao Sun; Fengqin Wang; Zhiyong Peng; Nanhui Jiang; Lianjiu Su (Molecular Biology Reports, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Spatiotemporal characteristics of high winds in Jilin Province during 1982–2021 - Xiao Wei; Kaiwei Li; Yunmeng Zhao; Yueting Yang; Guangzhi Rong; Ying Guo; Jiquan Zhang (International Journal of Climatology, 2023)
High winds are a type of catastrophic weather characterized by wind speeds over 10.8 m·s −1 , occurring in all seasons, and have become more frequent, impacting crop growth, agricultural production and quality of life. It is crucial to understand the spatial and temporal distribution patterns of high winds, as well as their speed and other characteristics, for logical planning of agricultural production and the creation of disaster resilience measures. This study applied the climate tendency, accumulative anomalies, theory of run, Mann–Kendall trend and Theil–Sen median to analyse the spatial and temporal distribution characteristics of the average wind speed and high wind days in Jilin Province, the probability of occurrence of high winds of various magnitudes in different eras, and the gale concentration degree (GCD) throughout Jilin Province for a total of 40 years from 1982 to 2021. The average wind speed and number of high wind days in Jilin Province have decreased over the past 40 years, and this trend has slowed over time. The average GCD in Jilin Province has shown an increasing trend over the last 40 years, with the average GCD being highest in Liouhe and lowest in Linjiang. In general, level six high winds were the main wind hazard level in Jilin Province, with the highest frequency occurring in different seasons and decades. In addition, the occurrence of high wind days is affected by global climate change and different underlying surfaces, which leads to maize and yield reduction. Research on the spatiotemporal distribution of high winds can provide important suggestions for the prevention and management of high wind disasters.

Dietary exposure risk assessment of pyrethroids in fruits and vegetables: a national scale investigation - Qianqian Li; Bei Li; Dawei Chen; Rong Zhang; Shuyan Liu; Shupeng Yang; Yi Li; Jianxun Li (Environmental Science and Pollution Research, 2023)

The spatial distribution, health risk, and cytotoxicity of metal(loid)s in contaminated field soils: The role of Cd in human gastric cells damage - Jiao-Yang Ma; Wei-Yu Li; Zi-Yue Yang; Jin-Zhou Su; Li Li; Yi-Rong Deng; Yun-Fei Tuo; You-Ya Niu; Ping Xiang (Science of The Total Environment, 2023)

Structure, stability, and potential function of groundwater microbial community responses to permafrost degradation on varying permafrost of the Qinghai-Tibet Plateau - Sining Zhong; Bin Li; Bowen Hou; Xuming Xu; Jinyun Hu; Rong Jia; Shanqing Yang; Shungui Zhou; Jinren Ni (Science of The Total Environment, 2023)

Quantum oscillations in field-induced correlated insulators of a moiré superlattice - Le Liu; Yanbang Chu; Guang Yang; Yalong Yuan; Fanfan Wu; Yiru Ji; Jinpeng Tian; Rong Yang; Kenji Watanabe; Takashi Taniguchi; Gen Long; Dongxia Shi; et al. (Science Bulletin, 2023)

The impact of inorganic ions on the solar photolysis of chlorinated dissolved organic matter from different sources: Spectral characteristics, disinfection byproducts, and biotoxicities - Yali An; Xiaoyan Y. Ma; Wenfeng Chen; Wei Li; Siyan Yang; Rong Chen; Xiaochang C. Wang (Journal of Hazardous Materials, 2023)

Comparative study of encapsulated cannabidiol ternary solid dispersions prepared by different techniques: The application of a novel technique jet milling - Hang Li; Tian-Xiao Yang; Qing-Sheng Zhao; Shou-Bu Hou; Rong-Rong Tian; Bing Zhao (Food Research International, 2023)

Genome resequencing reveals genetic loci and genes conferring resistance to SMV-SC8 in soybean - Jiahao Chu; Wenlong Li; Zhanwu Yang; Zhenqi Shao; Hua Zhang; Shaoda Rong; Youbin Kong; Hui Du; Xihuan Li; Caiying Zhang (Theoretical and Applied Genetics, 2023)

Receiver function imaging of dense seismic array and deep dynamic mechanism beneath the eastern South China - Rubing Han; Dinghui Yang; Qiusheng Li; Rong Huang; Hongshuang Zhang; Jiangtao Li; Hao Chen; Zhuo Ye; Wei Fu (Science China Earth Sciences, 2023)

Molecular Hydrogen Mediates Neurorestorative Effects After Stroke in Diabetic Rats: the TLR4/NF-κB Inflammatory Pathway - Wan-Chao Yang; Ting-ting Li; Qiang Wan; Xin Zhang; Li-Ying Sun; Yu-Rong Zhang; Pei-Chen Lai; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)
Diabetes is an independent risk factor for stroke and amplifies inflammation. Diabetic stroke is associated with a higher risk of death and worse neural function. The identification of effective anti-inflammatory molecules with translational advantages is particularly important to promote perioperative neurorestorative effects. Applying molecular hydrogen, we measured blood glucose levels before and after middle cerebral artery occlusion (MCAO), 48-h cerebral oedema and infarct volumes, as well as 28-day weight, survival and neurological function. We also measured the levels of TLR4, NF-κB p65, phosphorylated NF-κB p65, catecholamines, acetylcholine and inflammatory factors. All measurements comprehensively showed the positive effect and translational advantage of molecular hydrogen on diabetic stroke. Molecular hydrogen improved the weight, survival and long-term neurological function of rats with diabetic stroke and alleviated changes in blood glucose levels before and after middle cerebral artery occlusion (MCAO), but no difference in circadian rhythm was observed. Molecular hydrogen inhibited the phosphorylation of NF-κB and significantly reduced inflammation. Molecular hydrogen mediates neurorestorative effects after stroke in diabetic rats. The effect is independent of circadian rhythms, indicating translational advantages. The molecular mechanism is related to the TLR4/NF-κB pathway and inflammation. Graphical abstract Molecular hydrogen (H 2 ) affects outcomes of ischemic stroke with diabetes mellitus (DM).

Molecular detection and characterization of three novel parvoviruses belonging to two different subfamilies in zoo birds - Yan Wang; Yijie Sun; Xin Li; Rong Chen; Wang Li; Li Ji; Qifan Zhao; Likai Ji; Shixing Yang; Wen Zhang (Archives of Virology, 2023)

Leaf angle as a leaf and canopy trait: Rejuvenating its role in ecology with new technology - Xi Yang; Rong Li; Andrew Jablonski; Atticus Stovall; Jongmin Kim; Koong Yi; Yixin Ma; Daniel Beverly; Richard Phillips; Kim Novick; Xiangtao Xu; Manuel Lerdau (Ecology Letters, 2023)
Life on Earth depends on the conversion of solar energy to chemical energy by plants through photosynthesis. A fundamental challenge in optimizing photosynthesis is to adjust leaf angles to efficiently use the intercepted sunlight under the constraints of heat stress, water loss and competition. Despite the importance of leaf angle, until recently, we have lacked data and frameworks to describe and predict leaf angle dynamics and their impacts on leaves to the globe. We review the role of leaf angle in studies of ecophysiology, ecosystem ecology and earth system science, and highlight the essential yet understudied role of leaf angle as an ecological strategy to regulate plant carbon–water–energy nexus and to bridge leaf, canopy and earth system processes. Using two models, we show that leaf angle variations have significant impacts on not only canopy‐scale photosynthesis, energy balance and water use efficiency but also light competition within the forest canopy. New techniques to measure leaf angles are emerging, opening opportunities to understand the rarely‐measured intraspecific, interspecific, seasonal and interannual variations of leaf angles and their implications to plant biology and earth system science. We conclude by proposing three directions for future research.

CircBCL11B acts as a ceRNA to facilitate 1,2-dichloroethane-induced astrocyte swelling via miR-29b-3p/AQP4 axis in SVG p12 cells - Yizhou Zhong; Bingli Zhang; Yuji Huang; Jiaxin Du; Boxuan Liang; Zhiming Li; Rongyi Ye; Bo Wang; Hongyi Xian; Xifei Yang; Weifeng Rong; Xiang Guo; et al. (Toxicology Letters, 2023)

Abundant bacterial subcommunity is structured by a stochastic process in an agricultural system with P fertilizer inputs - Lei Liu; Li Zhu; Rong Yan; Yu Yang; Jonathan M. Adams; Jinshan Liu (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

Biochar enhanced organic matter transformation during pig manure composting: Roles of the cellulase activity and fungal community - Yanan Yin; Mengtong Li; Xiaohui Tao; Chao Yang; Wenrong Zhang; Haichao Li; Yucong Zheng; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2023)

Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

A pair of new oxindole alkaloids isolated from Uncaria macrophylla - Xin-Xin Liang; Jin-Xuan Yang; Jian-Mei Li; Jia-Bi Huang; Liu-Meng Yang; Tian-Tian Sun; Rong-Hua Luo; Wei-Lie Xiao; Yong-Tang Zheng; Xiao-Li Li (Natural Product Research, 2023)

The application of 3D printing technology on starch-based product: A review - Liyuan Rong; Xianxiang Chen; Mingyue Shen; Jun Yang; Xin Qi; Yulin Li; Jianhua Xie (Trends in Food Science & Technology, 2023)

Methane emission under straw return is mitigated by tillage types depending on crop growth stages in a wheat-rotated rice farming system - Zheng-Rong Kan; Yifan Li; Xinyu Yang; Silong Zhai; Yi Meng; Chaofan Xu; Jianying Qi; Feng-Min Li; Changqing Chen; Haishui Yang (Soil and Tillage Research, 2023)

Melanin synthesis gene Aapks contributes to appressorium formation, stress response, cell well integrity and virulence in Alternaria alternata - Rong Li; Wenyi Xu; Yuanyuan Zong; Xiaojin Wang; Yongcai Li; Yang Bi; Dov B. Prusky (Postharvest Biology and Technology, 2023)

TiO2/g-C3N4 photoanode prepared with polydopamine inspiration for photocatalytic fuel cells towards simultaneous wastewater treatment and electricity generation - Yuxin Liu; Lin Chen; Jinwang Li; Rong Chen; Xun Zhu; Dingding Ye; Yang Yang; Qiang Liao (Journal of Water Process Engineering, 2023)

Hollow urchin-shaped NCM811 ternary-structure for high rate charge/discharge capability and efficient CO2 adsorption - Fan-Ming Yang; Xiao-Yao Zhou; Xi-Da Li; Zhi-Cheng Yi; Rong Feng; Guo-Wen He (Journal of Environmental Chemical Engineering, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

Synergistic strategy design of (malonamide-amidoxime) bifunctional branching network crosslinked membrane and application in uranium (VI) resource recovery - Yang Li; Qi Ren; Rong Hua; Hong-Tao Xia; Xu-Xin Li; Ze-Yang Wang; Xuan Fu; Yan-Jun Du; Ze-Yi Yan; Yun Wang (Chemical Engineering Journal, 2023)

Bamboo-derived hydrophobic porous graphitized carbon for adsorption of volatile organic compounds - Yang Rong; Cong Pan; Kexin Song; Jong Chol Nam; Feng Wu; Zhixiong You; Zhengping Hao; Jinjun Li; Zhongshen Zhang (Chemical Engineering Journal, 2023)

Assessing the Coordinate Development Between Economy and Ecological Environment in China’s 30 Provinces from 2013 to 2019 - Bing Rong; Cheng-jun Chu; Zhen Zhang; Ya-ting Li; Shu-hao Yang; Qian Wang (Environmental Modeling & Assessment, 2023)

Kuroshio Intrusion Combined with Coastal Currents Affects Phytoplankton in the Northern South China Sea Revealed by Lipid Biomarkers - Yaoyao Wang; Rong Bi; Jiawei Gao; Hailong Zhang; Li Li; Yang Ding; Gui’e Jin; Meixun Zhao (Journal of Ocean University of China, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

First report of fruit rot caused by Paramyrothecium foliicola on muskmelon in China - Jian Fei Huo; Yong Xia Ren; Yu Rong Yao; Hai Yan Ben; Xiu Yun Wen; Wen Lai Ren; Li Juan Yang; Wan Li Wang; Yong Juan Hao (Journal of Plant Pathology, 2023)

Characterization of microbial community, ecological functions and antibiotic resistance in estuarine plastisphere - Le-Yang Yang; Xin-Rong Huang; Roy Neilson; Shu-Yi-Dan Zhou; Zhao-Lei Li; Xiao-Ru Yang; Xiao-Xuan Su (Science of The Total Environment, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Synergistic and antagonistic effects of preharvest salicylic acid and postharvest 1-methylcyclopropene treatments on the storage quality of apricot - Changchang Liang; Xinzhi Cui; Chanchan Sun; Sunxiang Ye; Ningxin Huang; Rong Chen; Aidi Zhang; Yanqing Yang; Hansheng Gong; Shuyang Sun; Fengjun Guo; Xinguang Fan; et al. (Food Chemistry, 2023)

Dual-functional electrostatic self-assembly nanoparticles enable suppressed defects and improved charge transport in perovskite optoelectronic devices - Hu Zhang; Pengfei Xu; Zhiliang Chen; Hengkai Zhang; Wenlong Shao; Yanhui Li; Jianfeng Yao; Da Rong; Duanwangde Liu; Liangpan Yang; Siliang Wang; Pengbin Gui; et al. (Chemical Engineering Journal, 2023)

Depth related variation of isoprenoid and hydroxylated tetraether lipids in Lake Lugu, Southwest China: Implications for palaeoenvironmental reconstructions - Jingjing Li; B. David A. Naafs; Rong Wang; Xiaoming Lai; Hao Long; Huan Yang; Xiangdong Yang (Chemical Geology, 2023)

Exploration of the link between gut microbiota and purinergic signalling - MingJian Li; BoWen Liu; Rong Li; Ping Yang; Ping Leng; Yong Huang (Purinergic Signalling, 2023)
Growing evidence reveals that microorganisms in the gut are linked to metabolic health and disease risk in human beings to a considerable extent. The focus of research at this stage must tend to focus on cause-and-effect studies. In addition to being a component of DNA and RNA, purine metabolites can be involved in purine signalling in the body as chemical messengers. Abnormalities in purinergic signalling may lead to neuropathy, rheumatic immune diseases, inflammation, tumors, and a wide range of other diseases. It has proved that gut microbes are involved in purinergic signalling. The relationship between these gut-derived purinergic signalling molecules and host metabolism may be one of the important clues to our understanding of the mechanisms by which the microbiota affects host metabolism.

A comparative study of soil nutrient availability and enzyme activity under biological soil crusts in different erosion regions of the Loess Plateau, China - Rong Hui; Huijuan Tan; Xinrong Li; Ruiming Zhao; Haotian Yang (Plant and Soil, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

Pipeline positioning by the surface-to-borehole electromagnetic induction method in a clayey deposit - Guo-Wei Li; Zhi-Ming Ye; Yang Zhou; Guan-Jun He; Guang-Yu Liu; Xin-Rong He (Applied Geophysics, 2023)

Radon exhalation from cement-based materials under accelerated carbonation - Rong Yang; Jie Wang; Xiaowen Zhang; Jie Li; Mianbiao Chen (Environmental Science and Pollution Research, 2023)

Straw incorporation interacting with earthworms mitigates N2O emissions from upland soil in a rice-wheat rotation system - Zheng-Rong Kan; Jiajia Zhou; Feng-Min Li; Mohamed S. Sheteiwy; Jianying Qi; Changqing Chen; Haishui Yang (Science of The Total Environment, 2023)

Biochar reduces bioavailability of phosphorus during swine manure composting: Roles of phoD-harboring bacterial community - Yanan Yin; Chao Yang; Mengtong Li; Sai Yang; Xiaohui Tao; Yucong Zheng; Xiaochang Wang; Rong Chen (Science of The Total Environment, 2023)

Novel one-point calibration strategy for high-throughput quantitation of microcystins in freshwater using LC-MS/MS - Huiyan Zhang; Yanshen Li; Mohamed F. Abdallah; Haiguang Tan; Jianxun Li; Shuyan Liu; Rong Zhang; Feifei Sun; Yi Li; Shupeng Yang (Science of The Total Environment, 2023)

An antioxidant lignan glycoside and triterpenoid saponins from the leaves of Synsepalum dulcificum - Xin-Peng Li; Jun-Fei Wang; Rong Huang; Tang-Chang Xu; Si-Si Liu; Qing-Rong Yang; Shao-Hua Wu (Phytochemistry Letters, 2023)

Synergistic enhancement of heat transfer and thermal storage characteristics of shell and tube heat exchanger with hybrid nanoparticles for solar energy utilization - Yangyang Wu; Jiancheng Rong; Di Wang; Xuefeng Zhao; Lan Meng; Müslüm Arıcı; Changyu Liu; Ruitong Yang; Dong Li (Journal of Cleaner Production, 2023)

Soil organic carbon regulates CH4 production through methanogenic evenness and available phosphorus under different straw managements - Zheng-Rong Kan; Zirui Wang; Wei Chen; Ahmad Latif Virk; Feng-Min Li; Jian Liu; Yaguang Xue; Haishui Yang (Journal of Environmental Management, 2023)

Fertility assessment and nutrient conversion of hydrochars derived from co-hydrothermal carbonization between livestock manure and corn cob - Chao-sheng Li; Rong-rong Cai; Abdulla Hasan; Xiao-luan Lu; Xiao-xiao Yang; Yan-guo Zhang (Journal of Environmental Chemical Engineering, 2023)

Novel polysaccharide from Panax notoginseng with immunoregulation and prebiotic effects - Hui-Rong Yang; Xue Li; Hao Liu; Dong-Rui Zhao; Ying-Jie Zeng (Food Bioscience, 2023)

Rapid charge transfer in covalent organic framework via through-bond for enhanced photocatalytic CO2 reduction - Li-Juan Gong; Li-Yao Liu; Shao-Shuai Zhao; Shuai-Long Yang; Duan-Hui Si; Qiu-Jin Wu; Qiao Wu; Yuan-Biao Huang; Rong Cao (Chemical Engineering Journal, 2023)

Highly efficient removal of aromatic diamines from the polyurethane bio-hydrolysate by MIL-53 series MOFs - Liyan Chen; Meng Rong; Jiemiao Yu; Qiyu Meng; Shan Ni; Xia Wu; Li Wang; Huifang Xing; Huizhou Liu; Liangrong Yang (Chemical Engineering Journal, 2023)

Molecular mechanisms of interrod spacing-mediated osseointegration via modulating inflammatory response and osteogenic differentiation - Meng Yu; Hongwei Yang; Bo Li; Rong Wang; Yong Han (Chemical Engineering Journal, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Community succession of microbial populations related to C N P S biological transformations regulates product maturity during cow-manure-driven composting - Xin Liu; Xiangmin Rong; Junyan Yang; Han Li; Wang Hu; Yong Yang; Guoliang Jiang; Rusheng Xiao; Xingxiang Deng; Guixian Xie; Gongwen Luo; Jiachao Zhang (Bioresource Technology, 2023)

A glyoxylate-containing benzene derivative and butenolides from a marine algicolous fungus Aspergillus sp. SCSIO 41304 - Xin Qi; Wei-Hao Chen; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Yong-Hong Liu; Jun-Feng Wang; Yong Li (Natural Product Research, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

DNA Methylation Alterations and Their Association with High Temperature Tolerance in Rice Anthesis - Bo Li; Haiya Cai; Ke Liu; Bingzhuang An; Rong Wang; Fang Yang; Changli Zeng; Chunhai Jiao; Yanhao Xu (Journal of Plant Growth Regulation, 2023)
DNA methylation is an important epigenetic mechanism involved in gene regulation under environmental stresses in plants. However, little information is available regarding its responses to high temperature (HT) and association with HT tolerance in rice. In this study, fourteen rice genotypes were classified into the susceptible, moderate, and tolerant groups by the high temperature susceptibility index (HTSI) after HT treatment. The changes of DNA methylation in rice anthesis under normal and HT30 conditions were investigated using methylation-sensitive amplified polymorphism31 (MSAP). The MSAP results showed that the DNA methylation level significantly increased in the susceptible rice group and decreased in the tolerant rice group under HT treatment, while no significant difference was observed in the moderate rice group. More hypomethylation events were detected in the tolerant rice group, while more hypermethylation was detected in the susceptible rice group. Forty-four differentially methylated epiloci (DME) were generated under both control and HT conditions, which can clearly distinguish the susceptible, moderate, and tolerant genotypes via PCoA analysis. Approximately 43.18% of DMEs were determined to be tolerance-associated epiloci (TAEs). 63.15% TAEs were sequenced and annotated into 12 genes. Quantitative RT-PCR analysis showed that 12 TAE genes were mainly upregulated in 14 rice genotypes, and their expression levels were related to the HT tolerance of rice. Here, DEGs, generated from a number of genotypes, indicate higher probabilities for association with stress tolerance. Overall, these results suggest that DNA methylation regulation might play a key role in adaptation to HT stress in rice.

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

Accidental acquisition of a rescued Japanese encephalitis virus with unspliced introns in the viral genome when using an intron-based stabilization approach - Ying Huang; Hongshan Xu; Shan Liu; Jiansheng Lu; Lili Jia; Yuhua Li; Rong Wang; Peng Yang; Yongxin Yu; Zhixin Yang (Archives of Virology, 2023)
The intron-based stabilization approach is a very useful strategy for construction of stable flavivirus infectious clones. SA 14 -14-2 is a highly attenuated Japanese encephalitis (JE) live vaccine strain that has been widely used in China since 1989. To develop safe and effective recombinant vaccines with SA 14 -14-2 as a backbone vector, we constructed the DNA-based infectious clone pCMW-JEV of SA 14 -14-2 using the intron-based stabilization approach and acquired the rescued virus rDJEV, which retained the biological properties of the parental virus. Unexpectedly, a rescued virus strain with altered virulence, designated rHV-DJEV, was accidentally acquired in one of the transfection experiments. rHV-DJEV showed up to 10 5 -fold increased neurovirulence compared with the SA 14 -14-2 parental strain. Genome sequencing showed that the inserted introns were still present in the genome of rHV-DJEV. Therefore, we think that the intron-based stabilization approach should be used with caution in vaccine development and direct iDNA immunization.

Divergence of epibacterial community assemblage correlates with malformation disease severity in Saccharina japonica seedlings - Yongwei Yan; Shanshan Wang; Kuimei Liu; Zhaolan Mo; Huichao Yang; Xiaojun Rong; Jie Li (Frontiers in Marine Science, 2023)
Malformation disease (MD) is one of the major constraints in the mariculture of the commercially important seaweed Saccharina japonica , which can cause severe losses of the kelp seedlings in the production process. However, the pathogenesis of MD remains largely undetermined. In this study, using cultivation experiments under laboratory conditions, MD severity was estimated for the young sporophytes of S. japonica , which were separately cultivated under different treatment conditions, including light intensity, duration of light exposure, and maturity level of the parent kelp. The associations between MD severity and epibacterial community divergence and assembly patterns were characterized. Higher MD severity significantly correlated with longer light exposure, and with both unmatured and overmatured parent kelp. The bacterial classes γ-Proteobacteria and α-Proteobacteria dominated all samples, but different MD severities were associated with different epibacterial communities. Comparisons of predicted functions for epibacterial communities revealed that longer light exposure led to a depletion in development and regeneration, while overmatured parent kelp resulted in a depletion in glycan biosynthesis and metabolism. Functional comparisons of the epibacterial communities between normal and unmatured parent kelp-generated seedlings revealed significantly different categories related to metabolism, environmental information processing, cellular processes, drug resistance, and bacterial infection. The significantly different pathways between groups, notably those related to bacterial infection and cellular processes, were partly consistent with the differences in bacterial compositions. The assembly of epiphytic bacterial communities was predominately governed by deterministic processes, and less impact was determined when there was significantly higher MD severity except when using overmatured parent kelp. Co-occurrence networks of the epibacterial communities associated with higher MD severity contained fewer nodes and exhibited lower modularity, but had higher graph density and degrees compared with those of seedlings with lower MD severity, indicating more complicated interactions. Nesterenkonia , Glycocaulis , Halomonas , Pseudoalteromonas , Pseudomonas , Loktanella , and Cobetia were frequently determined keystone taxa in communities associated with higher MD severity. The present study enhances our understanding of the factors significantly associated with MD severity and the potential roles of epimicrobiome in determining the disease severity, which will be useful for disease management in the future.

Enhanced phytoremediation of atrazine-contaminated soil by vetiver (Chrysopogon zizanioides L.) and associated bacteria - Faming Zhang; Shixian Sun; Yuhong Rong; Lili Mao; Shuchun Yang; Ling Qian; Rongbiao Li; Yi Zheng (Environmental Science and Pollution Research, 2023)

Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Yu-ru Chen; Rong-rong Sha; Xiao-li Sun; Xing-pan Guo; Yi Yang (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in the water samples collected from the Yangtze River Estuary and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community contributed the most (43.5%) to the ARG profiles, followed by dissolved metal ions (25.7%), MRGs, (19.4%), and MGEs (4.4%). Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli ) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes.

The growth performance, antioxidative status and muscle quality of grass carp (Ctenopharyngodon idellus) cultured in the recirculating pond aquaculture system (RPAS) - Weitong Xu; Qiushi Yang; Yin Wang; Rong Tang; Dapeng Li (Aquaculture, 2023)

Dye mineralization under UV/H2O2 promoted by chloride ion at high concentration and the generation of chlorinated byproducts - Bing Yang; Qiuping Luo; Qinman Li; Rong Jia; Yucheng Liu; Xiangfu Huang; Mi Zhou; Lingli Li (Science of The Total Environment, 2023)

Degradation of antibiotics by electrochemical advanced oxidation processes (EAOPs): Performance, mechanisms, and perspectives - Qingbin Yuan; Siyao Qu; Rong Li; Zheng-Yang Huo; Yan Gao; Yi Luo (Science of The Total Environment, 2023)

Trends in drought and effects on carbon sequestration over the Chinese mainland - Yang Li; Mengdi Li; Zhicheng Zheng; Wei Shen; Yanan Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Discovery of a fossil dwarf antelope outside of Africa and its implications for the late Miocene ecosystem in the northeast margin of the Tibetan Plateau - Shi-Qi Wang; Jimin Sun; Chunxiao Li; Shi-Jie Li; Jiao Fu; Qigao Jiangzuo; Luda Xing; Rong Yang (Gondwana Research, 2023)

Development and characterization of ultrastable emulsion gels based on synergistic interactions of xanthan and sodium stearoyl lactylate - Chunhuan Liu; Yunxing Li; Rong Liang; Hong Sun; Lei Wu; Cheng Yang; Yuanfa Liu (Food Chemistry, 2023)

Impacts of meteorological factors and ozone variation on crop yields in China concerning carbon neutrality objectives in 2060 - Beiyao Xu; Tijian Wang; Libo Gao; Danyang Ma; Rong Song; Jin Zhao; Xiaoguang Yang; Shu Li; Bingliang Zhuang; Mengmeng Li; Min Xie (Environmental Pollution, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Combining a novel biofilm reactor with a constructed wetland for rural, decentralized wastewater treatment - Rui Zhang; Xianchang Liu; Lutian Wang; Pan Xu; Kai Li; Xiaoxiao Chen; Rong Meng; Yuewu Pu; Xuetong Yang; Diederik P.L. Rousseau; Stijn W.H. Van Hulle (Chemical Engineering Journal, 2023)

A thin LiGa alloy layer from in-situ electroreduction to suppress anode dendrite formation in lithium-sulfur pouch cell - Rong Li; Liwen Yang; Lei Song; Changan Zhou; Jiayu Zhou; Ting Chen; Chen Wu; Yujia Zeng; Kui Ma; Hairong Yue (Chemical Engineering Journal, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Micro-mesoporous graphitized carbon fiber as hydrophobic adsorbent that removes volatile organic compounds from air - Min Yan; Yang Rong; Feng Wu; Zhixiong You; Dashan Wang; Xudong Yang; Zhengping Hao; Jinjun Li; Zhongshen Zhang (Chemical Engineering Journal, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Hominibacterium faecale gen. nov., sp. nov., an anaerobic l-arginine-degrading bacterium isolated from human feces - Noori Borhanudin; Min Yang; Andrei V. Chaplin; Jiang Li; Qiong Wang; Li-rong Dai; Ke-jia Wu; Shi-chun Ma; Boris A. Efimov; Lei Cheng (Archives of Microbiology, 2023)